Perspective of UPLB academic managers and administrators on leadership [sample] - Bumatay, Ernesto Laforteza (2010)
The study aimed to explore the perspectives of academic managers in the University of the Philippines Los Banos (UPLB) on leadership perspectives
Keywords: Educational leadership -- Evaluation; Transformational leadership